2013
DOI: 10.1007/978-1-4614-4711-5_15
|View full text |Cite
|
Sign up to set email alerts
|

c-Src and c-Yes are Two Unlikely Partners of Spermatogenesis and their Roles in Blood-Testis Barrier Dynamics

Abstract: Src family kinases (SFKs), in particular c-Src and c-Yes, are nonreceptor protein tyrosine kinases that mediate integrin signaling at focal adhesion complex at the cell-extracellular matrix interface to regulate cell adhesion, cell cycle progression, cell survival, proliferation and differentiation, most notably in cancer cells during tumorigenesis and metastasis. Interestingly, recent studies have shown that these two proto-oncogenes are integrated components of the stem cell niche and the cell-cell actin-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 168 publications
(179 reference statements)
0
31
1
Order By: Relevance
“…However, in these earlier reports, the downstream signaling molecules crucial to regulating endosomal sorting for the eventual recycling and/or degradation of endocytosed proteins remain unknown. Studies in c-Src and c-Yes, two members of the nonreceptor protein kinases, have illustrated their differential functions in cell physiology, in particular their roles in endocytic vesicular transport of proteins in other mammalian cells (34,39,49). For instance, c-Yes is monopalmitoylated, and it is transported from the Golgi pool of caveolin to plasma membrane to mediate endosome trafficking, illustrating its involvement in protein transcytosis; but c-Src is nonpalmitoylated, and it is shuffled between plasma membrane and late endosomes/lysosomes, suggesting that it may be intimately related to endosome-mediated degradation (11,34,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in these earlier reports, the downstream signaling molecules crucial to regulating endosomal sorting for the eventual recycling and/or degradation of endocytosed proteins remain unknown. Studies in c-Src and c-Yes, two members of the nonreceptor protein kinases, have illustrated their differential functions in cell physiology, in particular their roles in endocytic vesicular transport of proteins in other mammalian cells (34,39,49). For instance, c-Yes is monopalmitoylated, and it is transported from the Golgi pool of caveolin to plasma membrane to mediate endosome trafficking, illustrating its involvement in protein transcytosis; but c-Src is nonpalmitoylated, and it is shuffled between plasma membrane and late endosomes/lysosomes, suggesting that it may be intimately related to endosome-mediated degradation (11,34,39).…”
Section: Discussionmentioning
confidence: 99%
“…However, in these earlier studies, the underlying molecular mechanism(s) that affects targeting of the endocytic vesicles to the pathways of transcytosis and/or recycling vs. degradation remains unclear. Recently, multiple studies have shown that both of the closely related members of the Src family kinases, namely c-Src and c-Yes, are involved in endocytic vesicle-mediated trafficking of proteins in mammalian cells possibly via their regulations of the actin cytoskeleton (9,34), but the evidence was obscure as to how much they would perform overlapping functions in these events (49). We hypothesized that the Sertoli cell BTB utilized c-Yes and c-Src as the molecular "switches" in which c-Yes favors the targeting of the biotinylated and endocytosed BTB proteins for recycling vs. c-Src targeting the biotinylated and endocytosed proteins for intracellular degradation so that these two nonreceptor tyrosine kinases that work together provide a novel mechanism to regulate preleptotene spermatocyte transport across the BTB at stage VIII of the epithelial cycle.…”
mentioning
confidence: 99%
“…Thus, interactions of CTS with sodium pumps trigger through the activation of the c-Src/c-Raf/Erk1/2/CREB signalling cascade the increased expression of the TJ proteins claudin-1 and claudin-11 and stimulate TJ formation. Activation of Src family kinases (SFK) like c-Src or c-Yes is critical for the formation and the dynamics of the BTB (Xiao et al, 2012). Whereas in other epithelia and also at the BTB c-Src regulates cell adhesion via its effects on endocytic vesicle-mediated protein trafficking, both c-Src and c-Yes confer cell adhesion at the apical ectoplasmic specialisation and at the BTB either by sustaining the phosphorylation status of integral membrane proteins and their peripheral adaptors (Xiao et al, 2011(Xiao et al, , 2012 or by promoting the non-classical signalling pathway of testosterone (Walker, 2010), which also modulates cell adhesion in the seminiferous epithelium (Xiao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Gene knockout studies indicate that in the neurons of the developing brain, MARCKS is required for the targeting of N-cadherin and of β-catenin to the proper location within the plasma membrane of these highly polarized cell [75]. It is therefore noteworthy that both β-catenin and N-cadherin are expressed by Sertoli cells and are essential to male fertility [67,76]. 294 Sertoli Cell Biology …”
Section: A Kinase Anchoring Proteinsmentioning
confidence: 96%